Influences of Growth Durations on Characteristics of NaYF4:(Yb,Tm) Upconversion Materials - Dung, Nguyen Thi; Thanh, Hoang Van; Lam, Nguyen Dinh (VNU Journal of Science: Natural Sciences and Technology; Vol 35 No 4DO - 10.25073/2588-1140/vnunst.4965, 2019)
NaYF 4 :(Yb,Tm) upconversion materials  were synthesized by the simple hydrothermal method. Growth duration was varied from 4h to 12h under a growth temperature of 150 o C. The structural, optical and surface morphology characteristics of the NaYF 4 :(Yb,Tm) UC materials were investigated. The XRD and SEM results illustrated that the NaYF 4 :(Yb,Tm) materials were transformed from the multiple phases (hexagonal and cubic) to the single-phase (hexagonal prism) as growth duration being longer than 8h with the average diameter and length of these prisms being about 0.5 µm and 2 µm, respectively. Under 980 nm laser excitation, the NaYF 4 :(Yb,Tm) emits at peaks of 450 nm ( 1 D 2 → 3 F 4 ), 475 nm ( 1 G 4 → 3 H 6 ), 647 nm ( 1 G 4 → 3 F 4 ) and 697  nm ( 3 F 3 → 3 H 6 ), with the highest emission belonging to NaYF 4 :(Yb,Tm) grown for 8h. Keywords: NaYF 4 :(Yb,Tm), upconversion materials, photoluminescence, growth duration, hydrothermal method. References [1] L. Wang, R. Yan, Z. Huo, L. Wang, Fluorescence resonant energy transfer biosensor based on upconversion-luminescent nanoparticles, Angew. Chem. Int. Ed. Engl. 44 (2005) 6054-6057. https://doi.org/10.1002/anie.200501907. [2] S. N. Shan, X. Y. Wang, N.Q. Jia, Synthesis of NaYF4:Yb3+, Er3+ upconversion nanoparticles in normal microemulsions, Nanoscale Res. Lett. 6 (2011) 539-539. https://doi.org/10.1021/nl070235+. [3] T. Hinamoto, H. Takashima, H. Sugimoto, M. Fujii, Controlling Surface Plasmon Resonance of Metal Nanocap for Upconversion Enhancement, J. Phys. Chem. C 121 (2017) 8077-8083. https://doi.org/10.1021/acs.jpcc.7b01010. [4] Q. Guo, J. Wu, Y. Yang, X. Liu, J. Jia, J. Dong, Z. Lan, J. Lin, M. Huang, Y. Wei, Y. Huang, High performance perovskite solar cells based on β-NaYF4:Yb3+/Er3+/Sc3+@NaYF4 core-shell upconversion nanoparticles, J. Power Sources 426 (2019) 178-187. https://doi.org/10.1016/j. jpowsour.2019.04.039. [5] M.H. Huang, S. Mao, H. Feick, H. Yan, Y. Wiu, H. Kind, E. Weber, R. Russo, P. Yang, Room-temperature ultraviolet nanowire nanolasers, Science 292 (2001) 1897-1899. https://dx.doi. org/10.1126/science.1060367. [6] R. Gao, C. Hao, L. Xu, C. Xu, H. Kuang, Spiny Nanorod and Upconversion Nanoparticle Satellite Assemblies for Ultrasensitive Detection of Messenger RNA in Living Cells, Anal. Chem. 90 (2018) 5414-5421. https://doi.org/10.1021/ acs.analchem.8b00617. [7] M. Buchner, U. Ngoensawat, M. Schenck, C. Fenzi, N. Wongkaew, L. Colangelo, T. Hirsch, A. Duerkop, A. Baeumner, Embedded nanolamps in electrospun nanofibers enabling online monitoring and ratiometric measurements, J. Mater. Chem. C. 5 (2017) 9712-9720. https://doi. org/10.1039/c7tc03251j. [8] F. Wang, E. Banerjee, Y. Liu, X. Chen, X. Liu, Upconversion nanoparticles in biological labeling imaging and therapy, Analyst. 135 (2010) 1839-1854. https://doi.org/10.1039/c0an00144a. [9] H. S. Mader, P. Kele, S. M. Saleh, O. S. Wolfbeis, Upconverting luminescent nanoparticles for use in bioconjugation and bioimaging, Curr. Opin. Chem. Biol. 14 (2010) 582 596. https://doi. org/10.1016/j.cbpa.2010.08.014. [10] G. Yi, H. Lu, S. Zhao, Y. Ge, W. Yang, D. Chen, L. H. Guo, Synthesis Characterization and Biological Application of Size-Controlled Nanocrystalline NaYF4:Yb,Er Infrared-to-Visible Up-Conversion Phosphors, Nano. Letters 4 (2004) 2191-2196. https://doi.org/10.1021/ nl048680h. [11] F. Wang, J. Wang, X. Liu, Direct evidence of a surface quenching effect on size-dependent luminescence of upconversion nanoparticles, Angew. Chem. Int. Ed. Engl. 49 (2010) 7456-7460. https://doi.org/10.1002/anie.201003959. [12] M. Lin, M. Liu, M. Qui, Y. Dong, Z. Duan, Y. H. Li, B. P. Murphy, T. J. Lu, F. Xu, Synthesis of upconversion NaYF4:Yb3+,Er3+ particles with enhanced luminescent intensity through control of morphology and phase, J. Mater. Chem C 2 (2014) 3671-3676. https://doi.org/10.1039/c4tc 00129j. [13] K.W. Krämer, D. Biner, G. Frei, H. u. Gudel, M. P. Hehlen, S. R. Luthi, Hexagonal Sodium Yttrium Fluoride Based Green and Blue Emitting Upconversion Phosphors, Chem. Mater. 16 (2004) 1244-1251. https://doi.org/10.1021/cm 031124o. [14] G. Chen, T. Y. Ohulchanskyy, R. Kumar, H. Agren, P. N. Prasad, Ultrasmall monodisperse NaYF(4):Yb(3+)/Tm(3+) nanocrystals with enhanced near-infrared to near-infrared upconversion photoluminescence, A.C.S. nano 4 (2010) 3163-3168. https://doi.org/10.1021/nn 100457j. [15] S. Dühnen, T. Rinkel, M. Haase, Size, Control of Nearly Monodisperse β-NaGdF4 Particles Prepared from Small α-NaGdF4 Nanocrystals, Chem. Mater. 27 (2015) 4033-4039. https://doi.org/10.1021/acs.chemmater.5b01013. [16] T. Rinkel, J. Nordmann, A. N. Raj, M. Haase, Ostwald-ripening and particle size focussing of sub-10 nm NaYF(4) upconversion nanocrystals, Nanoscale 6 (2014) 14523-14530. https://doi.org/ 10.1039/C4NR03833A. [17] W. Huang, M. Dinh, H. Huang, C. Jiang, Y. Song, Y. Ni, C. Lu, Z. Xu, Uniform NaYF4:Yb, Tm hexagonal submicroplates: Controlled synthesis and enhanced UV and blue upconversion luminescence, Mater. Res. Bull. 48 (2013) 300-304. https://doi.org/10.1016/j.materresbull.2012. 10.031. [18] L. Wang, Y. Li, Na(Y1.5Na0.5)F6 Single-Crystal Nanorods as Multicolor Luminescent Materials. Nano Letters 6 (2006) 1645-1649. https://doi.org/ 10.1021/nl060684u. [19] J. Du, O. Q. D. Clercq, D. Poelman, Temperature depent persistent luminescence: Evaluating te optimum working temperature, Scientific Reports 9(2019) 10517. https://doi.org/10.1038/s41598-019-46889-z.